Facilitators and Barriers to Adapting to the Disease: The Lived Experience of Patients With Multiple Sclerosis - Shafigh Mehraban; Bahman Bahmani; Manouchehr Azkhosh; Mohammad Saeed Khanjani; Mojtaba Azimian (University of Social Welfare and Rehabilitation Sciences, 2023)
Objective Multiple sclerosis (MS) is a neurological disease in which the myelin lining the central nervous system is damaged. The complex nature of the disease making the diagnosis more difficult for the patient to face. This study explored the experiences of facilitators and barriers adjustment to MS by Iranian patients. Materials & Methods This study was conducted by using descriptive phenomenological approach. The participants included 14 patients (8 women and 6 men) referred to Rafideh Hospital in Tehran. The participants were selected by purposive sampling and maximum variety. Data collection continued through semi-structured interviews until theoretical saturation. The duration of the interviews was between 30-60 minutes. Data analysis was done with MAXQDA software and using the 7-step descriptive collaizzi,s method continuously and simultaneously with data collection. In order to check the robustness of the results, Lincoln and Goba criteria of validity, reliability, transferability and verifiability were used. Results The 5 main themes related to facilitators of adaptation that emerged included religious strategies, receive emotional and professional support, search and find information, psychological coping strategies, and life style (and 18 subcategories). Also the three main themes related to barrier of adaptation that emerged included health-related, patient-related and social-related barriers (and 8 subcategories). Conclusion These themes represent the perceived characteristics, facilitators and barriers of adaptation to Multiple Sclerosis by patients. Therefore, it is necessary to design or implement therapeutic interventions based on these findings by psychologists and counselors for patients to reduce psychological problems.